Diaspora Space in Alice Pung's Growing Up Asian in Australia - mega rahmadani (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
In this era lots of people around the world doing movement that is called as Diaspora. Diaspora is the movement, migration, or scattering of a people away from an established or ancestral homeland. In living abroad, people are usually away from their nativity just like in the native country. In maintaining the nativeness, the diasporian people showing their diaspora space as the key to have life like native. Diaspora space is a site where the native is as much a diasporian as the diasporian is the native. The anthology book entitled Growing up Asian in Australia gives lot of stories that related into the diasporian life through the struggling of being immigrant. This research emphasizes into two problems (1) how is diaspora space depicted in the story and (2) how does diaspora space shape the characters’ cultural identity. The research used social identity theory by Samovar in analysing the data to answer the statement of the problems. The data is the quotation from the story that related into the problem, and the source of the data is Growing up Asian in Australia book by Alice Pung. This research is qualitative research since using library research as the technique of analysis. The result shows that diaspora space does exists among the characters through their activities and later it is found that diaspora space holds significant contribution towards identity development.